The Impact of Changes in Basel Capital Requirements on the Resilience of African Commercial Banks - Damilola Oyetade; Adefemi A. Obalade; Paul-Francois Muzindutsi (Scientific Annals of Economics and Business)
Focusing on a panel sample of 41 commercial banks over the period of 2000-2018, this study examined the effect of capital adequacy on the resilience of commercial banks in Africa under changing Basel levels (II, III, and the proposed Basel IV). The study created sample representative banks for the proposed Basel IV and used two measures, namely Z-score and CAMELS, to capture bank resilience. Using the panel logistic regression and fixed effect model, we found that capital adequacy, liquidity, earnings management efficiency, and macroeconomic conditions are key determinants of the resilience of commercial banks in Africa. Additionally, Basel compliant banks tend to be less prone to macroeconomic factors. Based on the positive and significant impact of all Basel capital ratios on Zscore, the results suggest that a high level of capital requirements increases African banks' resilience, and banks with higher capital can absorb risk exposures.